2018
DOI: 10.1111/1365-2745.12962
|View full text |Cite
|
Sign up to set email alerts
|

An experimental extreme drought reduces the likelihood of species to coexist despite increasing intransitivity in competitive networks

Abstract: Very little is known about how variation in environmental conditions alters the strength and the structure of competitive networks and what are the consequences of this for species coexistence. We performed a competition experiment with 10 annual plant species to parameterise a population model describing species’ dynamics according to their vital rates and pairwise competitive coefficients. Seeds from all species were sown under two different climatic scenarios: (1) right before the first major storm of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 55 publications
10
93
0
Order By: Relevance
“…Matías et al. () show more intransitive competition under experimental drought conditions, confirming results from observational studies by Soliveres et al. () and Ulrich et al.…”
Section: How Does Intransitive Competition Affect Coexistence?supporting
confidence: 81%
See 4 more Smart Citations
“…Matías et al. () show more intransitive competition under experimental drought conditions, confirming results from observational studies by Soliveres et al. () and Ulrich et al.…”
Section: How Does Intransitive Competition Affect Coexistence?supporting
confidence: 81%
“…Gilpin () also suggested that intransitive competition should prevail in productive environments, especially in the tropics; however, in this issue, Matías et al. () and Soliveres et al. () refute this hypothesis using a variety of approaches.…”
Section: What Factors Determine Whether Species Compete Transitively mentioning
confidence: 98%
See 3 more Smart Citations